2015
DOI: 10.1016/j.polymer.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Real time optical and mechano-optical studies during drying and uniaxial stretching of Polyetherimide films from solution

Abstract: a b s t r a c tIn order to have a fundamental understanding of the temporal evolution of physical characteristics of Polyetherimide (PEI) film and processing parameters, real time measurements are essential. Because drying and stretching processes of solvent-cast polymer film are complex, off line measurements are unable to reveal the temporally varying detailed information, especially for fast "transient events". To solve the problem, two measurement systems, one for drying that tracks real time thickness, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…They concluded that at all rates the apparent demarcation from linearity in the strain optical constants corresponds to approximately 1.2 times the T g of PLA 13 . Jiang et al 39 showed the temporal evolution of physical characteristics of solution cast noncrystallizable polyetherimide films by uniaxial stretching. They found that initial linear elastic regime shrinks with the increase of solvent content indicating that the presence of solvents partially “melts” these rigid segmental correlations in T g –T ll range.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that at all rates the apparent demarcation from linearity in the strain optical constants corresponds to approximately 1.2 times the T g of PLA 13 . Jiang et al 39 showed the temporal evolution of physical characteristics of solution cast noncrystallizable polyetherimide films by uniaxial stretching. They found that initial linear elastic regime shrinks with the increase of solvent content indicating that the presence of solvents partially “melts” these rigid segmental correlations in T g –T ll range.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond a critical drying level, it rapidly increases to a high value around 10 min. These results on in-plane and out-of-plane birefringence indicate that the initially randomly oriented polymer chain axes lay down in the plane randomly as the thickness decreases during solvent evaporation . Thus, dried films attain uniaxial symmetry with optic axes oriented in the normal direction.…”
Section: Resultsmentioning
confidence: 79%
“…Figure 1a plane and out-of-plane birefringence indicate that the initially randomly oriented polymer chain axes lay down in the plane randomly as the thickness decreases during solvent evaporation. 30 Thus, dried films attain uniaxial symmetry with optic axes oriented in the normal direction. The films were found to be amorphous as the aromatic groups and side groups designed in this polymer make it easy to vitrify even when solidified from highly mobile solutions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation